Sementes de Piper L. (Piperaceae) do Parque Estadual da Serra da Tiririca (PESET), Niterói, Maricá, Estado do Rio de Janeiro, Sudeste do Brasil - Luciana Cavalcante de Moura; George Azevedo de Queiroz; Elsie Franklin Guimarães; Jorge Antônio Lourenço Pontes (Hoehnea)
RESUMO The Piperaceae family has a wide distribution and species richness, mainly in the Amazonian and Atlantic forests. In Brazil, there are 474 registered species distributed in the genera Manekia Trel., Peperomia Ruiz & Pav., and Piper L. The fruits are arranged in spikes, racemes or umbels of spikes, with bats being their main dispersers. The present study aimed to morphologically describe the seeds of Piper in the Parque Estadual da Serra da Tiririca, located in the State of Rio de Janeiro, in the municipalities of Niterói and Maricá. Seeds from herbariums were analyzed after being extracted from the fruit, cleaned, and photographed. Morphological characteristics such as seed shape, symmetry, and color were considered in order to assist in species determination and contribute to studies on bat diet.